Method for inhibiting space charges of insulation interface of direct-current cable factory joint based on electric field induction

By applying an external electric field during the insulation restoration process of high-voltage DC cable factory joints, the charge distribution and polarization state of the material are controlled, solving the problem of space charge accumulation at the insulation interface. This achieves significant uniformity of electric field distribution and improved lifespan, thus resolving the problem of interface charge distortion in existing technologies. The electric field-induced technology has been applied to solve the problems of electric field distortion and shortened insulation life caused by space charge accumulation in existing technologies, thereby improving the electrical performance and reliability of the cable.

CN120978494APending Publication Date: 2025-11-18HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511030793.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-25
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Space charge easily accumulates at the insulation interface of high-voltage DC cable factory joints, leading to electric field distortion and affecting electrical performance and insulation life. Existing processes have limited efficiency in space charge control and poor engineering adaptability.

Method used

An external electric field is applied during the insulation restoration and cooling process. The charge distribution and polarization state of the material are controlled by the electric field, forming a uniform electric field distribution, which avoids the agglomeration and moisture absorption problems of the nanoparticle spraying method.

Benefits of technology

It significantly suppresses the accumulation of space charge, improves the electrical stability of the interface, extends the service life of high-voltage DC cables, and has good engineering feasibility and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120978494A_ABST
    Figure CN120978494A_ABST
Patent Text Reader

Abstract

The invention discloses a direct-current cable factory joint insulation interface space charge suppression method based on electric field induction, and belongs to the technical field of cable insulation. The method comprises the following steps: heating a polymer insulating material to a molten state, injecting the polymer insulating material into a mold and pouring the polymer insulating material on an insulating surface of a cable body; an external electric field of 0.1-2 kV / mm is applied in the process of recovering insulation formation, and cooling is conducted at the speed of 0.1-10 DEG C / min after heat preservation induction; and when the temperature of the mold is reduced to 25-50 DEG C, the electric field is removed, and the factory joint with the interface space charge suppression performance is formed. The invention also relates to a direct-current cable factory joint structure prepared by adopting the method and a preparation device of the direct-current cable factory joint structure. According to the method, the interface structure between the recovery insulator and the body insulator is adjusted by applying the electric field, so that charge accumulation is effectively reduced, electric field distortion is reduced, and the electrical performance and reliability of the cable factory joint are improved. The method has the advantages of simple process, high controllability and easiness in practical engineering application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of power cable insulation technology, specifically to a method for suppressing space charge at the insulation interface of DC cable factory joints based on electric field induction, which belongs to the related technologies for cable manufacturing and insulation performance improvement in high voltage DC transmission systems. Background Technology

[0002] DC cables are a core component of high-voltage direct current (HVDC) transmission systems, widely used for the integration of offshore wind and solar power plants, as well as inter-regional and intercontinental energy interconnections. As transmission lines continue to extend, factory-fitted joints are typically used to connect multiple cable segments to meet the demands of long-distance cable laying.

[0003] Factory joints mainly consist of two parts: the cable body insulation, which is the original cross-linked polyethylene insulation layer of the cable; and the restoration insulation, which is an intermediate connecting insulation layer formed by injection molding between the body insulation layers. This restoration insulation is typically achieved by injecting a polyethylene / cross-linking agent blend into a mold in a molten state at high temperature, and then completing cross-linking and curing under specific temperature and pressure conditions. However, due to limitations in process conditions and material interface characteristics, structural regions with significant differences in thermal history and poor interfacial bonding can easily form between the body insulation and the restoration insulation, leading to the formation of a physical interface.

[0004] Under high-voltage direct current operating conditions, space charge easily accumulates in this insulation interface region, leading to electric field distortion, localized electric field enhancement, and consequently accelerating insulation material aging and inducing breakdown, severely impacting the long-term reliable operation of the cable. To address these issues, existing research primarily explores two aspects:

[0005] On the one hand, process optimization methods can be used to improve the interface structure. For example, some studies have proposed that increasing the pressure applied to the restoring insulation can effectively suppress interface defects (e.g., DOI:10.1109 / TPWRD.2025.3569307), or using surface treatment to reduce the roughness of the bulk insulation to enhance interface adhesion (e.g., DOI:10.1109 / TDEI.2022.3157905). Although such processes improve the physical bonding quality of the interface to some extent, their ability to control space charge behavior remains limited.

[0006] On the other hand, some scholars have attempted to introduce functional materials into the interface to achieve space charge suppression, such as spraying nanoparticles onto the bulk insulating surface to establish a carrier trapping mechanism near the interface (e.g., DOI:10.1016 / j.cej.2022.138874). Although experimental results show a certain suppression effect, the ease with which nanoparticles aggregate, absorb moisture, and have a difficult-to-control uniform distribution limit their widespread application in practical engineering.

[0007] In summary, existing technologies still face bottlenecks in improving the space charge suppression performance of the insulation interface of factory joints. There is an urgent need for a new method that is structurally simple, process-controllable, and capable of directly inducing charge behavior regulation during joint forming, in order to further improve the electrical stability of the interface and extend the service life of high-voltage DC cables. Summary of the Invention

[0008] To address the problem that existing high-voltage DC cable factory joints are prone to accumulating space charge at the insulation interface during operation, leading to electric field distortion and affecting electrical performance and insulation life, and that existing processes (such as increasing pressure, surface treatment, or spraying nanomaterials) have limited efficiency and poor engineering adaptability in controlling space charge, this invention proposes a method for suppressing space charge at the insulation interface of DC cable factory joints based on electric field induction.

[0009] This invention applies an external electric field during the insulation restoration and cooling process to actively control the charge distribution and polarization state of the material during melting and solidification, thereby significantly suppressing the accumulation of space charge and achieving a more uniform electric field distribution. This invention not only features a simple structure and adjustable process parameters, but also avoids the agglomeration and moisture absorption problems inherent in nanoparticle spraying methods, demonstrating good engineering feasibility and reliability.

[0010] In one embodiment of the present invention, a method for suppressing space charge at the insulation interface of a DC cable factory joint based on electric field induction is provided. The method includes the following steps: heating a polymer insulating material to a molten state, extruding it into a mold and pouring it onto the insulation surface of the cable tapered body; applying an external electric field with a field strength of 0.1 to 2 kV / mm during the insulation recovery process; maintaining the electric field for 0 to 60 minutes, and then cooling the mold at a rate of 0.1 to 10 °C / min; when the mold temperature drops to 25 to 50 °C, removing the external electric field to obtain the DC cable factory joint.

[0011] Furthermore, in the method, the applied electric field can be a constant electric field or an alternating electric field, and the specific type can be selected according to the actual system requirements.

[0012] In one embodiment of the present invention, the mold includes a heating jacket, a high-voltage electrode, and a high thermal conductivity insulating material, wherein the high-voltage electrode is connected to a high-voltage power supply, and the cable conductor is grounded; the heating jacket is used for mold temperature control, and the pressure between the restoration insulation and the body insulation is adjusted by an extruder.

[0013] Furthermore, the high-voltage electrode is preferably made of stainless steel, and the high thermal conductivity insulating material can be selected from any one of polyester film, polyimide film, or polytetrafluoroethylene film.

[0014] In a preferred embodiment of the present invention, the polymer insulating material is cross-linked polyethylene, low-density polyethylene, high-density polyethylene, polypropylene, or a mixture thereof.

[0015] Furthermore, the preferred melting and crosslinking temperatures of the polymer materials are as follows: the melting temperature of crosslinked polyethylene is 110–130°C, and the crosslinking temperature is 160–190°C; the melting temperature of low-density polyethylene is 110°C; the melting temperature of high-density polyethylene is 120–160°C; and the melting temperature of polypropylene is 160–170°C.

[0016] In one embodiment of the present invention, the field strength (E) of the applied electric field is... field ) and the melting temperature (T) of the polymer material melt There is a matching relationship between them, preferably satisfying the following ratio: T melt / E field =200~333 (℃·mm / kV), or equivalently, T melt / E field =0.003~0.005(kV / mm·℃) -1 Under optimal operating conditions, with a melting temperature of 160℃, the electric field strength is set to 0.3 kV / mm.

[0017] Furthermore, the mold is preferably cooled at a rate of 1–5 °C / min during the cooling process to achieve stable control of the interface structure.

[0018] In one embodiment of the present invention, a DC cable factory joint structure based on the above method is provided, including a cable conductor, a semiconductive shielding layer, a body insulation and a recovery insulation; wherein the recovery insulation is formed by an electric field induced process, and the interface between the recovery insulation and the body insulation has a low space charge density and a relatively uniform electric field distribution.

[0019] Optionally, the mold may also include an injection port and a terminal block, used for injecting molten insulating material and connecting a high-voltage power supply, respectively, to facilitate the establishment of a high-voltage field and automated process control.

[0020] Based on the above technical solution, the present invention provides a method for suppressing space charge at the insulation interface of DC cable factory joints based on electric field induction. By introducing a controlled external electric field during the melting and cooling process of the recovery insulation, the method guides molecular orientation, charge distribution and micro-polarization behavior at the key stage of interface structure formation, thereby effectively regulating the interface state between the bulk insulation and the recovery insulation.

[0021] In a preferred embodiment of the present invention, the electric field-induced process intervenes in the carrier migration and trapping mechanism at the polymer interface, thereby significantly reducing the space charge density in the interface region and avoiding the charge accumulation phenomenon caused by interface inhomogeneity in traditional methods.

[0022] Furthermore, by setting a reasonable electric field strength range (0.1–2 kV / mm) and matching it with different polymer melting temperatures, the resulting thermo-electric coupling control window can achieve optimal interface uniformity and polarization control. For example, using an electric field strength of 0.3 kV / mm at a melting temperature of 160°C can achieve significant improvements, including a 43.9% reduction in interfacial space charge density and a reduction in maximum electric field distortion rate of over 86.4%.

[0023] Another significant advantage of this invention is its simple process structure. The mold consists only of a conventional heating jacket, a high-voltage electrode, and a thin-film insulating material, which avoids the problems of agglomeration, moisture absorption, and uneven distribution caused by spraying nanoparticles in the prior art, while also taking into account ease of control and engineering feasibility.

[0024] Through the above methods, this invention not only improves the electrical performance and interface stability of factory-made joints, but also possesses good repeatability and adaptability, making it suitable for different types of polyethylene or polypropylene-based insulation material systems. This method provides effective technical support for the design and manufacture of factory-made DC cable joints with higher voltage levels and longer lifespans, and also lays a solid foundation for the long-term reliable operation of high-voltage DC transmission systems. Attached Figure Description

[0025] Figure 1 A schematic diagram of the mold structure for the electric field-induced DC cable factory connector manufacturing method used in this invention is shown;

[0026] Figure 2 This is a space charge distribution curve of Example 1 under the test condition of 40kV / mm;

[0027] Figure 3 This is a space charge distribution curve of Example 1 under the same test conditions;

[0028] Figure 4 This is a space charge distribution curve of Example 2 under the same test conditions;

[0029] Figure 5 This is a space charge distribution curve of Example 3 under the same test conditions;

[0030] Figure 6 This is a space charge distribution curve of Example 4 under the same test conditions;

[0031] Figure 7This is a graph showing the electric field distribution under the test conditions, as shown in Example 1.

[0032] Figure 8 This is the electric field distribution curve of Example 1;

[0033] Figure 9 This is the electric field distribution curve of Example 2;

[0034] Figure 10 This is the electric field distribution curve of Example 3;

[0035] Figure 11 This is the electric field distribution curve of Example 4;

[0036] Figure 12 This is a bar chart showing the average space charge volume density measured after 60 minutes of polarization for the control example and each embodiment.

[0037] Figure 13 This is a comparison chart of the maximum electric field distortion rate measured after 60 minutes of polarization between the control example and each embodiment.

[0038] Attached figures are labeled as follows: 1-Injection port; 2-Heating jacket; 3-High thermal conductivity insulating material; 4-Terminal; 5-Semi-conductive shielding layer; 6-Cable insulation; 7-Cable conductor; 8-High voltage electrode; 9-Restore insulation. Detailed Implementation

[0039] To make the technical solution of the present invention clearer and more complete, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0040] like Figure 1 As shown, a mold for manufacturing DC cable connectors based on electric field induction mainly includes an injection port 1, a heating sleeve 2, a high thermal conductivity insulating material 3, a terminal block 4, a semi-conductive shielding layer 5, cable body insulation 6, a cable conductor 7, a high-voltage electrode 8, and restoring insulation 9. The heating sleeve 2 is used to regulate the mold temperature, the high-voltage electrode 8 is connected to a high-voltage power supply, the cable conductor 7 is grounded, and the high thermal conductivity insulating material 3 in the mold structure achieves a balance between electrical isolation and heat conduction.

[0041] Example 1:

[0042] This embodiment provides a method for fabricating DC cable joints in a factory based on electric field induction, used to simulate the structure of actual factory joints and evaluate the ability of the electric field induction process to regulate space charge behavior. The method includes the following specific steps:

[0043] Step 1: Preparation of polymer insulating material blends

[0044] Low-density polyethylene (LDPE, melt temperature approximately 110°C) was selected as the base resin, and 1 part by weight of dicumyl peroxide (DCP) was added as a crosslinking agent. The mixture was stirred in an internal mixer at 110°C and 60 rpm for 3 minutes to ensure uniform dispersion of the crosslinking agent in the polymer matrix. The resulting blend was used to simulate actual injection molding materials for cable insulation restoration.

[0045] Step 2: Prepare equivalent test specimens of cable body insulation

[0046] A polyester film is laid on a clean, dry iron plate, and a polyester film mold measuring 100mm × 100mm × 0.125mm is placed on top. 1.25g of LDPE / DCP blend is placed into the mold cavity, and a second layer of polyester film and another iron plate are then placed on top, forming a sandwich-like layered structure. To achieve electrical insulation and ensure sample integrity, an additional layer of polyester film is placed between the upper iron plate and the hot-pressing platform. This film serves as an insulating medium between the upper electrode and the heating device during subsequent electric field induction, preventing breakdown and ensuring high-voltage safety.

[0047] The above structure is placed in a flat vulcanizing machine for hot-press crosslinking treatment:

[0048] Preheat at 110℃ for 15 minutes (without pressure) to allow the sample to heat up to a uniform molten state.

[0049] The pressure was gradually increased to 5MPa, 10MPa, and 15MPa, with each stage held for 5 minutes to simulate the gradual pressing process, eliminate air bubbles, and improve interface adhesion.

[0050] Finally, the temperature is raised to 175℃ and held for 30 minutes to complete the peroxide cross-linking reaction, forming a dense cable body insulation equivalent sample.

[0051] After demolding and cooling, the bulk insulation sample is placed in a 70°C vacuum oven for 24 hours to degas it. The purpose is to remove residual volatile components and crosslinking byproducts to prevent them from interfering with the space charge distribution in subsequent tests.

[0052] Step 3: Restore the insulating electric field to induce shaping

[0053] The above-mentioned bulk insulation sample was embedded in another polyester mold (100mm×100mm×0.25mm), and the same mass (1.25g) of LDPE / DCP blend was poured onto its upper surface. The sample was then covered with a polyester film and an iron plate to form a restorative insulation-bulk insulation composite structure.

[0054] The structure was placed in a flat vulcanizing machine, and the following hot-press induced crosslinking procedure was performed:

[0055] Preheat at 110℃ for 15 minutes (0MPa) to allow the insulation to initially melt.

[0056] Increase the pressure to 5MPa and hold it for 5 minutes to enhance the interfacial contact density;

[0057] After heating to 175℃, the temperature is kept constant while an electric field is applied: the upper iron plate is connected to a high-voltage DC voltage source and the lower iron plate is grounded, forming a constant electric field with a field strength of 0.1kV / mm, which is applied continuously for 30 minutes.

[0058] The electric field acts on the interface region where the insulation is still in the melting and cross-linking reaction stage, and has a guiding effect on the molecular chain rearrangement, polarization orientation and interface stress release process, which helps to suppress carrier traps and charge accumulation.

[0059] After crosslinking is completed, the cooling process is started. The mold temperature is reduced to about 50°C by free cooling or controlled cooling rate (no active rate is set in this example). Then the high voltage power supply is turned off, the electric field is removed, and the factory joint equivalent sample is demolded and taken out.

[0060] Finally, the sample was placed in a 70°C vacuum oven for 24 hours to degas it, in order to eliminate residual small molecules and moisture from the crosslinking process and ensure the stability of the charge test.

[0061] This embodiment constructs an equivalent sample of a factory connector with a well-defined interface structure and introduces an electric field-induced variable during its molding process to provide a parameter comparison basis for subsequent embodiments. The electric field strength used (0.1 kV / mm) is a low-value induction condition, mainly used to verify whether it possesses the initial effect of space charge modulation.

[0062] Example 2: Interface polarization optimization process based on a moderate electric field strength of 0.3 kV / mm

[0063] Based on Example 1, this embodiment adjusts the applied electric field strength to 0.3 kV / mm to study the effect of regulating the space charge behavior of the recovery insulation interface under moderate electric field induction conditions.

[0064] The process flow is as follows:

[0065] S201. Material and Mold Preparation

[0066] Completely consistent with Example 1, an equivalent sample of cable body insulation was constructed using an LDPE / DCP blend and subjected to vacuum degassing treatment.

[0067] S202. Restoration of insulation shaping and electric field induction

[0068] After casting the same mass of LDPE / DCP blend onto the cable body insulation surface, assemble the mold structure. Place this structure in a flat vulcanizing machine and execute the following procedures sequentially:

[0069] Preheating: Heat at 110℃ for 15 minutes (without pressure) to allow the insulation to initially melt;

[0070] Pressurization: Increase the pressure to 5 MPa and maintain it for 5 minutes to enhance interfacial contact;

[0071] Increase temperature: Continue increasing the temperature to 175℃;

[0072] Electric field application: At this temperature, a constant DC electric field with a strength of 0.3 kV / mm is applied for 30 minutes. The upper electrode is connected to a high-voltage power supply, and the lower electrode is grounded to create a stable electric field environment.

[0073] S203. Cooling and Post-treatment

[0074] After naturally cooling to 50°C, the electric field was removed and the sample was demolded. The sample was then placed in a 70°C vacuum oven for degassing for 24 hours.

[0075] The interface structure formed under these conditions exhibits excellent space charge suppression capabilities. PEA test results show that the charge density distribution tends to be smoother, and the electric field distortion is significantly reduced. Figure 9 and Figure 13 The results show that the sample under these conditions exhibits minimal electric field curve fluctuations and the lowest electric field distortion rate, thus proving to be the optimal combination of induction conditions for this invention.

[0076] Example 3: Electric Field-Induced Interface Control Method Based on 0.5kV / mm High Polarization Response

[0077] To verify the improvement of interface performance by stronger electric field induction, this embodiment increases the applied electric field strength to 0.5 kV / mm, which is in the preferred range (Tmelt / Efield = 320) in the "electric field-temperature matching window" to explore the effect of higher intensity induction in the "electric-thermal coupling window".

[0078] The process flow is as follows:

[0079] S301. Material and Sample Preparation

[0080] The materials are the same as in Example 1, and the hot pressing and degassing of the body insulation are completed.

[0081] S302. Restoration of the insulation electric field induced process

[0082] Preheating: Heat at 110℃ for 15 minutes (without pressure);

[0083] Pressurization: Increase the pressure to 5 MPa and maintain it for 5 minutes;

[0084] Heating: After reaching 175℃, apply a constant DC electric field of 0.5kV / mm to the upper and lower poles of the mold and maintain it for 30 minutes to ensure that the electric field plays a full role in the insulation melting and cross-linking stage.

[0085] S303. Cooling and Post-treatment

[0086] After the mold cools naturally to 50°C, the electric field is removed, the mold is demolded, and the mold is degassed under vacuum at 70°C for 24 hours.

[0087] Under this electric field strength, the polymer chain segments exhibit high polarization, significant interfacial polarization orientation, reduced trap density, and a good effect in suppressing space charge accumulation. Figure 6 and Figure 10 The results showed that the charge peak was significantly lower than that of the control group, the electric field distribution was more uniform, and the interface electrical performance was greatly improved.

[0088] However, although the induction conditions yielded good results, they had certain shortcomings in terms of engineering adaptability compared to Example 2 (0.3 kV / mm), such as higher equipment requirements and increased risk of electrical breakdown. Therefore, considering both overall performance and practical feasibility, Example 2 represents the recommended preferred parameter for this invention.

[0089] Example 4: Electric Field-Induced Interface Control Method Based on 0.7kV / mm High Polarization Response

[0090] This embodiment is used to explore the induction limit and process stability under a higher electric field. The electric field strength used is 0.7kV / mm, and other operating procedures are consistent with those in Embodiment 1.

[0091] A high-voltage DC power supply is connected to the upper plate electrode via an insulated connecting wire and is equipped with an overvoltage protection device. During the electric field induction period, special care should be taken to prevent the mold insulation layer (such as polyimide film or polytetrafluoroethylene film) from breaking down.

[0092] After 30 minutes of high-field induction followed by cooling and demolding, the sample was degassed and then tested for electrical properties. Although this condition still shows certain advantages in terms of space charge distribution control, from the perspective of practical engineering operation, the 0.7kV / mm induction condition places high demands on the strength of the mold structure and the breakdown voltage margin, which is not conducive to batch application in the field.

[0093] Therefore, while high-field induction can further enhance the polarization guidance effect, it also carries risks related to reduced controllability and increased costs, hindering engineering compatibility. Ultimately, it was determined that the conditions in Example 2 were more suitable as the preferred parameter combination for engineering application.

[0094] Compare with Example 1: No electric field induced condition

[0095] To evaluate the actual regulatory effect of the electric field-induced mechanism on the space charge behavior at the interface of DC cable factory joints, this embodiment uses the same materials, molds, molding processes and parameters as in Embodiment 1, except that no external electric field is applied during the insulation recovery molding stage, and is used as a control group.

[0096] Material preparation and body insulation molding

[0097] LDPE and DCP were blended at a mass ratio of 100:1 at 110°C for 3 minutes to obtain a restorative insulating injection molding material. Following the steps in Example 1, equivalent bulk insulation samples were prepared, including multi-stage pressure crosslinking (preheating at 110°C, staged pressing at 5 / 10 / 15 MPa, crosslinking at 175°C for 30 minutes) and vacuum degassing at 70°C for 24 hours to ensure consistent basic interface conditions.

[0098] Restoration of insulation casting and molding

[0099] The above-mentioned bulk insulation sample was embedded in a polyester mold, and 1.25g of homologous blend was poured onto its surface. The mold was covered with polyester film and iron plate on both sides and placed in a flat vulcanizing machine, where the following hot pressing process was performed:

[0100] Preheat at 110℃ for 15 minutes (without pressure);

[0101] Increase the pressure to 5MPa and maintain it for 5 minutes;

[0102] After heating to 175℃, continue to keep warm for 30 minutes to complete the insulation cross-linking reaction.

[0103] Unlike Example 1, no high-voltage power supply was connected during the molding process, meaning no external electric field (0 kV / mm) was applied to the mold. The interface between the cable's restored insulation and the main insulation was completely under natural thermosetting conditions, without any external inducing factors.

[0104] After cooling to room temperature, the sample was demolded and placed in a 70°C vacuum oven for 24 hours to degas, thus obtaining the control sample.

[0105] Purpose and significance of the test:

[0106] The control sample, serving as a non-electric field-induced baseline sample, participated in the same space charge testing procedure as Examples 1-4 (applying a DC voltage of 40 kV / mm) to compare the interface space charge distribution and electric field distortion under different electric field-induced conditions.

[0107] from Figure 2 and Figure 7 It can be seen that the control sample 1 exhibits significant space charge accumulation near the interface between the restored insulation and the bulk insulation, and the electric field distribution is highly distorted. Analysis shows that hot-pressing alone cannot adequately improve the interface polarization state and carrier behavior control, further verifying the significant advantages of the electric field-induced mechanism proposed in this invention in regulating the electrical properties of the insulation interface.

[0108] Space charge testing and comparative analysis

[0109] To verify the effect of the electric field-induced process on the control of space charge behavior at the insulation interface of the factory joint, this invention uses the pulsed electro-acoustic (PEA) method to systematically test the space charge distribution of the samples in Examples 1-4 and Control Example 1. All samples were polarized at a constant DC voltage of 40 kV / mm for 60 minutes, and their internal charge distribution characteristics and electric field response were measured.

[0110] The PEA (Potential Energy Equivalent) method is the most widely used method for measuring space charge in solid insulating media. The PEA test principle is as follows: Under a high electric field, space charge is formed inside the insulating medium. During testing, a pulsed voltage is applied to the test sample, establishing a pulsed electric field at the speed of light within the insulating medium. This pulsed electric field acts on the space charge at different locations, creating pulsed pressure that generates sound waves. The sound signal propagates at the speed of sound through the medium to the bottom electrode of the test sample. A piezoelectric sensor installed at the bottom of the lower electrode converts the sound wave signal into an electrical signal. After amplification and data acquisition, the test system outputs a voltage signal and stores it in the computer as data. The amplitude of the voltage signal is positively correlated with the space charge density at a specific location, and the time interval between different voltage signals corresponds to the location of the space charge. The distribution of space charge in the medium is obtained through voltage signal-time-difference spectrum analysis.

[0111] For plate specimens, the basic physical model and measurement theory of PEA, as well as the corresponding measurement technology, are now basically clear. The experimental technology is also basically mature and finalized, and IEC and JB standards have been formed. Therefore, it can be promoted and applied in the industry.

[0112] In this invention, the space charge suppression performance is evaluated using the following two quantitative indicators:

[0113] The first is the average space charge density, which measures the overall charge accumulation within the thickness range of the sample. Its calculation formula is as follows:

[0114]

[0115] Where Q represents the average space charge volume density (unit: C / m³). 3 L is the sample thickness, i.e., the distance between the upper and lower electrodes (unit: m), L = x2 - x1, ρ(t,x) is the space charge density at position x inside the sample at polarization time t (unit: C / m). 3 ).

[0116] Second, the maximum electric field distortion rate (η) max This is used to reflect the internal electric field deviation caused by charge distribution, and its expression is:

[0117]

[0118] Among them, Emax (t,x) represents the maximum electric field intensity inside the sample during the test, E ave The theoretical average electric field corresponding to the applied constant DC voltage (40 kV / mm in this test). This indicator can be used to evaluate the degree of localized enhanced electric field at the interface and is an important reference for judging the stability of insulation.

[0119] The introduction of the above two indicators provides a quantitative basis for analyzing the performance differences between the embodiments of the present invention, ensuring that the space charge control effect is measurable and repeatable.

[0120] Charge distribution results ( Figures 2 to 6 ):

[0121] like Figure 2 As shown, in Comparative Example 1, there is obvious bipolar charge accumulation in the interface region (where the bulk insulation and restoration insulation meet), exhibiting a symmetrical distribution of positive and negative charges. This indicates that carrier migration is restricted at the interface, resulting in charge retention, which can easily lead to electric field distortion and local aging.

[0122] In contrast, Examples 1-4 ( Figures 3 to 6 Under the same test conditions, as the applied electric field strength increases, the peak value of space charge near the interface decreases significantly and the distribution profile gradually becomes flatter, indicating that the electric field-induced process can effectively promote the homogenization of interface polarization, reduce trap density, and suppress charge accumulation.

[0123] Especially in Example 2 (0.3kV / mm), the charge in the interface region is significantly reduced, and the charge density tends to be consistent with that of the outer layer of the interface, showing excellent charge suppression effect.

[0124] Comparison of electric field distributions Figures 7 to 11 ):

[0125] To further evaluate the impact of space charge on electric field stability, Figures 7 to 11 The electric field distribution curves inside each sample are shown.

[0126] Compare with Example 1 ( Figure 7 At the interface, the electric field is severely distorted, and the local electric field strength is much higher than the average value, which poses a risk of electrical breakdown. In contrast, the electric field curve in the embodiment is smoother, the interface transition is more natural, and the degree of distortion is greatly reduced.

[0127] It is worth noting that in Example 2 ( Figure 9 In this process, the electric field curve exhibits minimal fluctuations and a nearly linear distribution, with the interface electric field uniformity reaching its optimal state. This verifies the advantages of a moderately strong induced electric field (0.3 kV / mm) under these process conditions.

[0128] Average charge density and electric field distortion variation analysis ( Figure 12 and Figure 13 ):

[0129] Figure 12 and Figure 13 The average space charge volume density and the maximum electric field distortion rate (η) of each group of samples were compared. max ).

[0130] The results show:

[0131] In Comparative Example 1, the space charge density is higher and the maximum electric field distortion rate is also significant, reflecting its insufficient interface polarization control capability.

[0132] In Examples 1-4, all samples outperformed the control group in both of the above two indicators, demonstrating the positive inhibitory effect of the electric field-induced strategy on charge behavior;

[0133] Among them, Example 2 achieved the best performance: the average space charge volume density was reduced by about 43.9% compared with the control group, and the maximum electric field distortion rate was reduced by about 86.4%, indicating that its interface structure was more stable and the carrier distribution was more uniform.

[0134] The test results clearly demonstrate that applying a moderate external electric field during the insulation recovery process can effectively guide the molecular alignment and polarization direction at the interface, reduce the probability of carrier trap formation, and thus improve the space charge behavior and electric field stability at the interface.

[0135] Especially in the range of 0.3 to 0.5 kV / mm, the induction effect matches well with the material crosslinking performance and thermal gradient distribution, providing a quantitative basis for the preferred range of the electric field induction window of this invention.

[0136] It should be understood that the embodiments disclosed in this specification are only used to illustrate the principles and technical solutions of the present invention, and do not constitute a limitation on the scope of protection of the present invention. Although the present invention has been described in detail with reference to specific embodiments, those skilled in the art can still make equivalent substitutions or improvements to the structural form, parameter selection, process flow, etc. of the present invention without departing from the spirit and substance of the present invention, and these equivalent modifications or substitutions should also fall within the scope of protection of the present invention.

Claims

1. A method for suppressing space charge at the insulation interface of a DC cable factory joint based on electric field induction, characterized in that, Includes the following steps: S10. Heat the polymer insulation material to a molten state, extrude it into a mold, and pour it onto the surface of the tapered cable body insulation. S20. Apply an external electric field with a field strength of 0.1 to 2 kV / mm during the insulation recovery process; S30. After maintaining the electric field for 0 to 60 minutes, cool the mold at a rate of 0.1 to 10 °C / min. S40. When the mold temperature drops to 25-50℃, remove the external electric field to obtain the DC cable factory connector.

2. The method according to claim 1, characterized in that: The applied electric field is either a constant electric field or an alternating electric field.

3. The method according to claim 1, characterized in that: The mold includes a heating jacket, a high-voltage electrode, and a high thermal conductivity insulating material; wherein the high-voltage electrode is connected to a high-voltage power supply, and the cable conductor is grounded; the heating jacket is used for temperature control, and the pressure between the restoration insulation and the main body insulation is adjusted by the extruder.

4. The method according to claim 3, characterized in that: The high-voltage electrode is made of stainless steel, and the high thermal conductivity insulating material is a polyester film, a polyimide film, or a polytetrafluoroethylene film.

5. The method according to claim 1, characterized in that: The polymer insulation material is cross-linked polyethylene, low-density polyethylene, high-density polyethylene, polypropylene, or a mixture thereof.

6. The method according to claim 5, characterized in that: The melting temperature of cross-linked polyethylene is 110–130℃, and the cross-linking temperature is 160–190℃. The melting temperature of low-density polyethylene is 110℃; The melting temperature of high-density polyethylene is 120–160℃; The melting temperature of polypropylene is 160–170℃.

7. The method according to claim 1, characterized in that: The matching relationship between the applied electric field strength and the melting temperature of the material satisfies: The optimal solution corresponds to a field strength of 0.3 kV / mm and a melting temperature of 160℃.

8. The method according to claim 1, characterized in that: During the cooling process, the mold is cooled at a rate of 1 to 5 °C / min.

9. A DC cable factory connector structure manufactured based on the method of any one of claims 1 to 8, characterized in that, It includes a cable conductor, a semi-conductive shielding layer, body insulation, and recovery insulation; wherein the recovery insulation is formed by an electric field-induced process and has a uniform electric field distribution and a low space charge density at the interface with the body insulation.

10. The structure according to claim 9, characterized in that: The mold also includes an injection port and a terminal block, used for injecting molten insulating material and connecting a high-voltage power supply, respectively.